Canva-based E-comic on the Dangers of Plastic Waste Environment as Learning Media for IPAS Effectively Improve Learning Outcomes - Ma'rifah Kulsum; Barokah Isdaryanti (Jurnal Penelitian Pendidikan IPA, 2024)
The decline in IPAS learning outcomes and focus on the material on the dangers of plastic waste is indicated by the unawareness of disposing of waste in its place. The purpose of this study was to develop Canva-based E-comics on the material of the Dangers of Plastic Waste for the Environment as an Effective IPAS Learning Media to Improve Learning Outcomes. The subjects used were fifth grade students of SDN Ngijo 01 Semarang. The method used is development research with the ADDIE model. Data collection used interviews, observations, tests, and questionnaires. Data analysis used descriptive and inferential statistical techniques. Development through five stages namely analysis, design, development, implementation, and evaluation. The results of media feasibility included a feasible category based on the assessment of material experts, media experts, linguists, and teacher and student response questionnaires. The effectiveness of e-comic is in the effective category to be used based on the increase in student learning outcomes after using this media. The conclusion is that the Canva-based e-comic media developed is valid, feasible, and effective in the teaching and learning process of the material on the dangers of plastic waste in IPAS subjects.